Editorial: Special Issue on Multi-scale Computational Methods for Solids and Fluids ECCOMAS MSF 2025 - Ibrahimbegovic, Adnan; Nikolić, Mijo (European Journal of Computational Mechanics, 2026)
This special issue contains six selected papers first presented in short for- mat at the 7th International Conference ECCOMAS MSF 2025 Multi-scale Computational Methods for Solids and Fluids, organized in Dalmatian capital Split, Croatia, 25–27 June 2025.